2023
DOI: 10.1021/acs.jpcc.3c00162
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Geometric Surface Area of Mesoporous Materials

Abstract: Specific surface area is an important property of porous materials and a crucial index in multiple disciplines, which is mainly measured using nitrogen isotherms and the Brunauer–Emmett-Teller (BET) equation. The BET surface area is remarkably higher than the geometric surface area, which is defined as the surface area of the crystal geometry structure. However, many studies directly use the BET surface area as the geometric surface area. We proposed a simple, general, and accurate method that only needs the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Numerous chemical and biological processes take place at or very close to a material's surface, making precise measurements of this area essential in many scientific and engineering fields. There are few previous studies where it has been shown that ML can accurately predict the surface areas of few systems with a very high accuracy rate [56–58] . In this manuscript, we were motivated by the significance of these goal attributes to attempt the development of a universal model that can accurately predict all of the target properties using a single set of inputs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous chemical and biological processes take place at or very close to a material's surface, making precise measurements of this area essential in many scientific and engineering fields. There are few previous studies where it has been shown that ML can accurately predict the surface areas of few systems with a very high accuracy rate [56–58] . In this manuscript, we were motivated by the significance of these goal attributes to attempt the development of a universal model that can accurately predict all of the target properties using a single set of inputs.…”
Section: Resultsmentioning
confidence: 99%
“…There are few previous studies where it has been shown that ML can accurately predict the surface areas of few systems with a very high accuracy rate. [56][57][58] In this manuscript, we were motivated by the significance of these goal attributes to attempt the development of a universal model that can accurately predict all of the target properties using a single set of inputs.…”
Section: Choice Of Target Propertiesmentioning
confidence: 99%
“…This is an interesting finding since many reports found that grain boundaries of perovskites often contain numerous defects, and they are detrimental to the device performance. [38][39][40] Steady-state photoluminescence (PL) spectra shows no significant wavelength shift in the irradiated films (Figure 2a) while there is a small shift in the CL result for samples of 1e13 p cm À2 fluence. Based on Figure S4, Supporting Information, we detected the CL peaks of 776.0, 775.8, 786.0, and 775.2 nm for fresh sample, and 1e12, 1e13, and 1e14 p cm À2 , respectively.…”
Section: Perovskite Films Under Proton Radiationmentioning
confidence: 99%
“…Microscopically, dissipative coupling results from the traveling‐wave‐induced cooperative external coupling. [ 44–46 ] Nair et al. proposed a bistability scheme in a cavity magnonics system with dissipative coupling by utilizing Kerr effect.…”
Section: Introductionmentioning
confidence: 99%